Estrategias de marketing post covid 19 para la reactivación económica de restaurantes del centro de la ciudad de Manta - Verduga Vélez, Eddy Ronaldo (2022)
The main objective of this research was to establish post-Covid-19 marketing strategies for the economic reactivation of restaurants in Manta city center, this being descriptive with a quantitative approach, where 3 phases were developed. First, a situational tourism diagnosis was carried out, which allowed identifying the general characteristics and current status of the tourist area, in addition, 31 F&B establishments were characterized through surveys directed at the owners of the restaurants, where the economic losses related to Covid-19 were analyzed. Then a market study was carried out analyzing the supply, demand and competition of the restaurants, an analysis of the demand was also carried out through the application of 384 surveys, resulting in the visitor prioritizing biosecurity in the quality and price of the gastronomic variety, in the study of the offer it was identified that most restaurants do not have websites among other applications. After that, the competitive profile matrix was developed to determine the current competition, in addition, the internal and external aspects were analyzed to determine the critical and relevant nodes, through the SWOT. Finally, three strategic objectives were carried out where digital marketing strategies were established, aimed at programs and projects, strategic actions were also developed to comply with the objectives set for the economic reactivation of restaurants. Finally, marketing strategies aimed at promotion and marketing are established through digital tools, allowing a wide gastronomic offer to be offered.